Expanding the Authority of Muhtasib to Protect Consumers: A Comparison between Moroccan Law and Islamic Qanun of Aceh - Ezzerouali, Souad (Faculty of Law Universitas Trunojoyo Madura, 2025)
The institution of Hisbah has historically played a fundamental role in organizing public life in Islamic societies through the principle of enjoining good and forbidding evil. This study examines the potential for integrating Hisbah into modern legal systems to strengthen social control, consumer protection, and environmental preservation. The research aims to clarify the legal and legitimate nature of Hisbah, explore its historical decline—particularly after the colonial era—and propose strategies for its rehabilitation. Using a historical, descriptive, and analytical approach, the study investigates the Moroccan legal framework governing Hisbah, assessing whether the Moroccan legislature has effectively integrated it into contemporary law. Additionally, the study compares Morocco's Hisbah system with the model in Aceh Province, Indonesia, where the institution has been successfully adapted to modern societal needs. The findings highlight the strengths and weaknesses of the Moroccan framework and suggest that legislative inflation may have hindered Hisbah’s effectiveness. Drawing lessons from Aceh, the study recommends revitalising Hisbah in Morocco, particularly in addressing contemporary challenges such as health, environmental protection, consumer rights, and traditional crafts.